2019
DOI: 10.1093/mnras/stz1357
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic spiral structure as revealed by O- and early B-type stars

Abstract: We investigate the morphology and kinematics of the Galactic spiral structure based on a new sample of O-and early B-type stars. We select 6,858 highly confident OB star candidates from the combined data of the VST Photometric Hα Survey Data Release 2 (VPHAS+ DR2) and the Gaia Data Release 2 (Gaia DR2). Together with the O-B2 stars from the literature, we build a sample consisting of 14,880 O-and early B-type stars, all with Gaia parallax uncertainties smaller than 20 per cent. The new sample, hitherto the lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 42 publications
4
44
0
4
Order By: Relevance
“…The green, pink and blue dashed lines mark respectively a possible spur 'Lower Sagittarius-Carina Spur', the 'split' found by Lallement et al (2019) and the spur identified by Xu et al (2016). Three black dashed circles mark the positions of three possible hole patterns in the Sagittarius and Perseus Arms identified in Chen et al (2019a). The Sun, assumed to be at the position of (X, Y, Z) = (´8.34, 0, 0) kpc, is located at the centre of the plot.…”
Section: Comparison With Previous Workmentioning
confidence: 88%
See 4 more Smart Citations
“…The green, pink and blue dashed lines mark respectively a possible spur 'Lower Sagittarius-Carina Spur', the 'split' found by Lallement et al (2019) and the spur identified by Xu et al (2016). Three black dashed circles mark the positions of three possible hole patterns in the Sagittarius and Perseus Arms identified in Chen et al (2019a). The Sun, assumed to be at the position of (X, Y, Z) = (´8.34, 0, 0) kpc, is located at the centre of the plot.…”
Section: Comparison With Previous Workmentioning
confidence: 88%
“…A significant fraction of the clouds concentrated in the direction of the Galactic anti-centre (l " 180˝), where the masers and OB stars also clump. Although several molecular clouds are visible in the two 'holes' repoted by Chen et al (2019a), the 'holes' are less populated by the clouds than in other areas.…”
Section: The Galactic Spiral Structure As Traced By the Molecular Cloudsmentioning
confidence: 93%
See 3 more Smart Citations